Evaluation of outer retinal layers in diabetic macula edema treated with intravitreal ranibizumab - Nur Aqilah Salleh,; Wong, HS; Syed Zulkifli SZ,; Mushawiahti Mustapha, (Pusat Perubatan Universiti Kebangsaan Malaysia, 2018)
Anti-vascular endothelial growth factor (VEGF) reduces choroidal thickness by choroidal hypoperfusion in diabetic macula oedema (DME) patients. Indirect effect of anti-VEGF towards outer retinal layers (ORL) which supplied by choroidal circulation has not been well described. We evaluate the ORL thickness between retinal pigment epithelium (RPE) with inner-segment-outer-segment photoreceptor junction (IS/OS) and RPE with external limiting membrane (ELM) in pre- and postintravitreal Ranibizumab (IVR) treated eyes with central foveal diabetic macula edema. A total of 60 eyes (40 patients) were analysed. ORL thickness measured with optical coherence tomography at pre- and post-injection day 1, week 4 and week 6. Mean thickness of RPE-IS/OS was statistically significant over time (p=0.023) but not for RPE-ELM (p=0.216). Thickness ratio between RPE-IS/OS and RPE-ELM and central subfoveal thickness (CST) both showed statistically significant result over time with p=0.038 and p=0.000, respectively. We observed an initial reduction of ORL thickness at day 1 followed by increased in thickness at week 4 with subsequent reduction at week 6 was observed. ORL is an aspect that can be explore and emphasized further in patients considered for IVR injections. The long-term effects of IVR to the ORL however could not be concluded due to short follow up period.